Redevelopment of a Dense Area: A Participatory Planning Approach for Regeneration in Old Dhaka, Bangladesh - Ahmad Ilderim Tokey; Shefa Arabia Shioma; Md. Muniruzzaman Munir; Dipita Hossain; Mohammad Shakil Akther; Ishrat Islam (Journal of Regional and City Planning, 2020)
Urban redevelopment is a critical process that needs to apporach issues from different angles with the intention to arrive at one single point: sustainability. Dhaka, the capital of Bangladesh, with a density of 28,000 people/km2, is currently having a tough time to give its people access to urban facilities. Old Dhaka, the 400-year-old part of the city, has very distinctive characteristics: historical buildings, wholesale trade, a dense urban pattern, narrow roads, low standard of urban utilities. This study attempted to describe persisting problems and expectations of the local people in this area, to be considered during redevelopment. This study followed the method of Participatory Rural Appraisal (PRA). First, the existing development pattern and business zones were determined based on a historical timeline, a transact walk, a social and resource map, and a mobility map. The pair-wise ranking method was used in several focus group discussions to prioritize the problems. After prioritizing, a cause-effect diagram was created for the top problems. Then, after a rigorous SWOT analysis, several strategies were formulated from the point of view of historical conservation, development pattern, and the existing chemical industry. The importance of this study is that it is a real-time study and that it has some general implications for similar future cases, such as prioritizing the most persistent problems, thinking with empathy while dealing with old, traditional areas and to ensure local safety, livability and business performance simultaneously in the case of commercial areas. The results of this study are useful for local policy makers as they provide a valuable blend of technical analysis and local people's feedback.Abstrak. Pembangunan kembali perkotaan adalah proses kritis yang perlu menangani masalah yang datang dari sudut yang berbeda dengan maksud untuk bertemu pada satu titik, keberlanjutan. Dhaka, ibu kota Bangladesh dengan kepadatan 28.000 orang/persegi. km, mengalami kesulitan untuk memberikan akses ke fasilitas perkotaan kepada warganya. Bagian Dhaka yang berusia 400 tahun, Old Dhaka memiliki karakteristiknya sendiri; bangunan bersejarah, perdagangan grosir, pola perkotaan yang padat, jalan sempit, standar utilitas perkotaan yang rendah. Studi ini mencoba untuk menggambarkan masalah yang ada dan harapan masyarakat lokal di daerah ini yang dapat dipertimbangkan selama pembangunan kembali. Ini mengikuti metode teknik Participatory Rural Appraisal (PRA). Pada awalnya pola pengembangan dan zona bisnis yang ada ditentukan oleh transact walk dan peta sosial dan sumber daya, garis waktu historis, dan peta mobilitas. Untuk memprioritaskan masalah, metode pemeringkatan berpasangan digunakan oleh beberapa Diskusi Kelompok Terarah (FGD). Setelah memprioritaskan, diagram sebab-akibat dibuat untuk masalah utama. Kemudian setelah analisis SWOT yang teliti, beberapa strategi diusulkan dari sudut pandang konservasi historis, pola pembangunan, industri kimia yang ada. Studi ini sangat penting karena ini adalah studi waktu nyata. Selain itu, ini menarik beberapa implikasi umum untuk kasus masa depan yang serupa seperti memprioritaskan masalah yang paling bertahan, berpikir dengan empati saat menangani kota tua yang tradisional dan untuk memastikan keamanan lokal, kelayakan hunian dan kinerja bisnis secara bersamaan ketika kasus tersebut berada di area komersial. Studi ini sangat penting bagi pembuat kebijakan lokal karena studi ini merupakan perpaduan yang bagus antara analisis teknis dan masukan masyarakat lokal.Kata kunci. Perencanaan partisipatif, PRA, pembangunan kembali, Dhaka Lama.